Implementation of Assemblr EDU in Early Childhood Education: Teacher’s Perspective - Khoerunnisa, Salsabila (Aulad: Journal on Early Childhood, 2025)
This research discusses the implementation of Assemblr Edu in early childhood education which aims to find out the views and efforts of teachers in implementing learning through Assemblr Edu. The approach used in this research is a qualitative approach using the case study method. The results showed that; (1) The background of PGRI Purworejo Kindergarten and Anak Sholeh Mojosari Kindergarten teachers utilising the Assemblr EDU application is by attending training, besides that teachers also feel many benefits and advantages so that the objectives in utilising the Assemblr EDU application as a learning media are maximally achieved; (2) The efforts of teachers in utilising the Assemblr EDU application include planning, implementing and evaluating learning; (3) The obstacles felt by teachers in utilising the Assemblr EDU application include the intensity of using the Assemblr EDU application and the lack of available facilities such as the internet and mobile phones as supporting tools.